Resveratrols from the stembark of shorea ovalis (meranti kepong) (dipterocarpaceae) and antioxidant activity / Rosmawati Abdul Aziz and Norizan Ahmat - Abdul Aziz, Rosmawati; Ahmat, Norizan (Universiti Teknologi MARA Cawangan Pahang, 2018)
Dipterocarpaceae is a plant family of large tree that is widely distributed in the tropical rain forest of Southeast Asia, such as Borneo and Peninsular Malaysia. Shoreais the largest genus of Dipterocarpaceae and the most economically important in Malaysia. Locally, Shoreais known as Balau, Meranti Pa’ang, Meranti Damar Hitam and Red Meranti. Shorea ovalis is the species included in the group of Red Meranti. Locally it is known as Meranti Kepong. Currently, very limited chemical constituents have been reported from this species. In this research, a phytochemical study was conducted on the stem bark of Shorea ovalis. The powder of the cleaned, chopped and grinded stem-bark was extracted using acetone viamaceration. The isolation and purification of the compound were carried out using vacuum liquid chromatography followed by radial chromatography and preparative thin layer chromatography. The structure of the pure compounds was elucidated by means of spectroscopic methods including NMR, UV- Vis, FTIR and comparison with literature. Two compounds were isolated and identified as resveratrol and α-viniferin. Resveratrol was reported for the first time for this plant. α-viniferin that has been previously reported, was subjected to antioxidant activity. However, this compound did not show significant antioxidant property